Powdery Mildew of Gerbera Daisy - Catalina Moyer; Natalia A. Peres (EDIS)
PP-257, a 4-page illustrated fact sheet by Catalina Moyer and Natalia A. Peres, describes this important fungal disease of gerberas in Florida, its symptoms, development, and management practices. Includes a table of fungicides registered to control powdery mildew on ornamentals in Florida. Published by the UF Department of Plant Pathology, July 2008.